Studies on Synthesis, Characterization, and Adsorption of Cationic Dyes from Aqueous Solutions Using Magnetic Composite Material from Natural Clay in Central Kalimantan, Indonesia - I Made Sadiana; Karelius Karelius; Retno Agnestisia; Abdul Hadjranul Fatah (Universitas Jenderal Soedirman, 2018)
Clay is a natural material from crystalline silicate with layered structures, has high cation exchange capacity, and large surface area. These advantages can be used as an adsorbent for the removal of contaminants in aqueous solutions, such as heavy metals and dyes. In Indonesia, clays from Java, Sulawesi, and Sumatra islands have been used as adsorbent, furniture, and construction materials. Due to limited information about basic characteristics of clay from Kalimantan, this clay has not been utilized well. Therefore, natural clay from Kalimantan, especially in Central Kalimantan, was used as adsorbent of cationic dyes in this present study. However, the clay has difficulty for separating the solid phase from aqueous solution after adsorption process. To solve this problem, combining clay with magnetic material was opted. The objectives of this study are to synthesize the magnetic composite material from natural clay by coprecipitation method and to characterize the synthesized magnetic composite material using an x-ray diffraction method, transmission electron microscopy, and vibrating sample magnetometer. The adsorption properties of the synthesized magnetic composite material were evaluated using rhodamine B and methylene blue dyes in aqueous solution. Before magnetic composite material was synthesized, the clay was previously being activated for removing impurities. The magnetic material formed in the structure of clay had magnetite with particle size of 2.75 nm and the magnetization value of 24.91emu/g. The adsorption capacities of natural clay, activated clay, and magnetic composite of clay in rhodamine B were 34.29, 76.27, and 81.46 mg/g, respectively, while in methylene blue were 30.25, 83.92, and 133.90 mg/g, respectively. These results suggested that magnetic composite of clay can increase the adsorption capacities against dyes and accelerate the separation of the adsorbent solid phase from aqueous solution with largest adsorption capacity on methylene blue dye.